ARM Assembly language programming Using Keil Development Tools Introduction - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
Manufacturers of CPUs publish a document that contains information about the processor that includes: list of registers, function of each register, size of data bus, size of address bus and list of instructions that can be executed by the CPU. Each CPU has a known instruction set that a programmer can use to write assembly language programs. Instruction sets are specific to each type of processor. That being said, Pentium processors use a different instruction set than ARM processors. Using the Instructions a of processor to write a program is called assembly language and function of an assembler is to convert assembly language to machine code (binary) that the CPU can understand.
Keywords: dept.csc